ISNAR Annual Report 2000 - International Service for National Agricultural Research (International Service for National Agricultural Research, 2001)
ISNAR's Director General, Stein W. Bie, reflects on trends in the management of agricultural research during the last decade. He considers ISNAR's annual report essays of the last decade to see whether ISNAR picked up the major changes early and forcefully enough. The report also gives an outline of ISNAR's activities and publications in 2000 and a financial report